Fermentabilitas dan Kecernaan in Vitro Ransum Limbah Agroindustri yang Disuplementasi Kromium Anorganik dan Organik - A Jayanegara; A S Tjakradidjaja; T Sutardi (Faculty of Animal Science, Bogor Agricultural University, 2006)
Chromium is a trace element which has been considered essential for humans and animals since 1959. However, the effect of chromium on activity of rumen microorganisms has not been yet investigated. This experiment was conducted to determine the effect of chromium supplementation to agroindustrial waste based diets on rumen microorganisms which was measured in vitro. Chromium supplement was in the form of anorganic and organic incoroporated to Rhizopus sp. fungus. Two experimental designs were used in this experiment. A completely randomized design with 10 treatments and 3 replications was used to measure dry matter and organic matter digestibilities (DMD and OMD). A factorial randomized block design 10 x 3 was used to measure total VFA and NH3 productions. Factor A was diet treatments and Factor B was fermentation period. Rumen fluid was used as block (replication). Treatments consisted of K1 (control diet), K2 (K1 + non mineral Rhizopus sp. fungus), A (K2 + anorganic Cr) with 4 levels of anorganic Cr (1, 2, 3, and 4 ppm), and O (K1 + organic Cr) with 4 levels of organic Cr (1, 2, 3, and 4 ppm). Incubation period was carried out for 1, 3, and 5 hours. The addition of non mineral Rhizopus sp. fungus (K2) decreased total VFA production from 110 to 59 mM (P < 0.05) and increased NH3production from 9.97 to 13.28 mM (P < 0.05). Supplementation of anorganic Cr decreased DMD and OMD compared to K2 (P < 0.05), but organic Cr supplementation increased DMD and OMD. Optimum level of organic Cr supplementation was 1 ppm and 4 ppm for anorganic Cr. This means that supplementation of organic Cr is four times more efficient than that of anorganic Cr. Key words : chromium, anorganic, organic, digestibility, fermentation